Finality and Binding Force of Constitutional Court Decisions: An Analysis of Original Intent and Executory Problematics in the Judicial Review of Law - Nawawi, Muhammad Rashif Abdillah; Maharesi, Izzan Altaf; Mardhatillah, Chayyra (CV. Social Politic Genius (SIGn), 2025)
The final and binding nature of Constitutional Court decisions in the judicial review of Law was designed as a power-balancing instrument to limit the arbitrariness of lawmakers. This generally binding force, in reality, clashes with the absence of an executory apparatus instrument, thereby engendering an executory procedural law vacuum at the related Law level. This research aims to discover the essential meaning of the decision’s binding force by tracing constitutional history, while simultaneously conducting a juridical analysis of the executory problematics to formulate follow-up governance that guarantees legal certainty. This normative legal research employs the statutory, conceptual, and historical approaches to analyze legal materials deductively. The research results indicate that the original intent of the amendment framers placed constitutional court decisions as an absolute control tool against the domination of lawmaker institutions. However, the deletion of the decision follow-up time limit has legitimized institutional arrogance, culminating in the phenomenon of constitutional disobedience. Legislative and executive actions that deliberately revive unconstitutional norms prove the exploitation of loopholes in executive governance weaknesses. The resolution to this problem demands a comprehensive restructuring that integrates a progressive judicial order approach with legislative obligations. The conclusion of this research affirms the urgency of amending Law Number 12 of 2011 to insert the obligation to institutionalize constitutional court decisions into the National Legislative Program, with a maximum time limit of one year, in order to sever the chain of disobedience by positive lawmakers.